(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Education and upbringing, as a subject of the pedagogy in the wider meaning of the term, have always been of special social and state interest. The state, with its instruments of government, has strived to carry out its politics in the field of education and upbringing. The word politics is associated with the terms state, state affairs, affairs of a state’s interest. This interest is very explicitly expressed in the function and the structure of the school and the school system, especially for satisfying the fundamental needs of every state. In this paper some interpretations of the terms politics of education and education policy are given, pointing out the differences in their treatment and meaning. It has been stressed that pedagogy has an autonomous position regarding the state’s educational- upbringing policy and the political factors, exponents of this policy. It has critical attitude towards the politics and the political conception of the goals, and is also autonomous from the educational-upbringing practice, having a critical attitude towards it too, since any educational-upbringing practice cannot be a source of pedagogical cognition and raise to the level of theory which, from that position, is going to advance the pedagogical practice. In this respect the issue of the correlation between politics and pedagogy is reviewed by their structure: policy (educational-upbringing policy), pedagogy (science, theory), educational-upbringing practice (pedagogical practice). In these processes and correlations there must be a permanent questioning and valorisation of the educational-upbringing policy, especially of its goals and educational strategy and practice, as well as of the postulates, models and instruments the pedagogy as a science offers. The realization of the goals in the development of educational- upbringing systems must be compatible with the directions of the development of education at global level, but nevertheless, the success depends on the social, cultural, economic and educational context of the particular state.